Risk Management Analysis To Improve Employee Performance At Pt Solusi Bangun Indonesia Tbk Cilacap-Central Java - Zaelani Adnan, Ahmad; Agung Pribadi, Farkhan; Ahman, Eeng; Disman, Disman; Yuniarsih, Tjutju (Riviera Publishing, 2022)
Currently, the industry in Indonesia is experiencing very rapid growth. Rapid industrial growth must balance efforts to control the possibility of potential hazards in the workplace. In Indonesia, occupational safety and health have a solid legal basis. All parties must implement them, whether workers, organizations or other related parties, to protect all parties. One of the efforts made to prevent hazards in the workplace is to improve occupational safety and health standards by implementing hazard identification and risk assessment. The study aims to analyze risk management to improve employee performance. It uses the direct observation method, namely by obtaining data directly at the company, and the literature study method, which gathers information by collecting literacy and reviewing the literature results based on the facts. When the risk is successfully suppressed as small as possible, it can reduce the potential danger posed and provide a sense of security and improve employee performance and productivity in working in the company. Risk Management on the employees' performance in PT Solusi Bangun Indonesia Tbk, Cilacap-Central Java, has a substantial and significant influence. It is hoped that further researchers can use the study result as reference material for research related to job satisfaction and information or complementary studies.